(untitled) (El Taco en la Brea, 2023)
The purpose of this paper is to analyze in certain tango lyrics by Celedonio Flores the uses of melodrama in the configurations of masculine pain and upward social mobility as central topics of this genre (Karush, 2013). We postulate as a hypothesis that, while from the kingdom of feelings basted in the mass-circulation serial (Sarlo, 2011) the woman was queen and captive, another sentimental empire is consolidated in the Buenos Aires tango circuit, in tango lyrics in general and in those of Flores in particular. We will analyze the imaginaries that unfold in his lyrics and the ways in which in tango, as a ritual, he invents and outlines an associated male figure, destined for the working class and endows passions with politicism, undoing the affective binomial between knowing and feeling (Macón, 2021), and shaping gender roles and relations between men and women.